2018
DOI: 10.1002/jca.21673
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura: A 5‐year tertiary care centre experience

Abstract: Introduction Thrombotic thrombocytopenic purpura (TTP) is associated with high mortality if not managed timeously with therapeutic plasma exchange (TPE). TTP secondary to human immunodeficiency virus (HIV) infection is unique to sub‐Saharan Africa. The management and outcome of TTP in the era of improved access to therapy has not been described. Methods The present study describes the clinical presentation, treatment, therapeutic endpoints, and outcome of TTP patients at the Charlotte Maxeke Johannesburg Acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
2
20
0
6
Order By: Relevance
“…Yapılan çalışmalarda insidansı milyon kişi başına 1 ile 13 olarak belirtilmektedir, kadınlarda daha sıkdır. Genellikle 30-40 yaşlarında daha sık görülür, [1,2] çocuklarda konjenital formlar ortaya çıkabilir. [2] TTP konjenital veya edinsel olabilir.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Yapılan çalışmalarda insidansı milyon kişi başına 1 ile 13 olarak belirtilmektedir, kadınlarda daha sıkdır. Genellikle 30-40 yaşlarında daha sık görülür, [1,2] çocuklarda konjenital formlar ortaya çıkabilir. [2] TTP konjenital veya edinsel olabilir.…”
Section: Discussionunclassified
“…Genellikle 30-40 yaşlarında daha sık görülür, [1,2] çocuklarda konjenital formlar ortaya çıkabilir. [2] TTP konjenital veya edinsel olabilir. TTP, ADAMTS-13 enziminin azalması veya yokluğuna bağlı olarak gelişir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…We believe LDH value is an important indicator of plasmapheresis response in the early term. Median plasmapheresis time was 8.5 days (range, 5-85); Swart et al [15] reported median plasmapheresis time of 10.0. Seven separate parameters including plasmic score, [8] platelet count, degree of hemolysis, presence of cancer, lack of transplantation, Mean corpuscular volume (MCV) value, international normalized ratio (INR), and creatinine allow evaluation of prognosis in patients with severe ADAMTS13 deficiency.…”
Section: Discussionmentioning
confidence: 99%